Association of a rare NOTCH4 coding variant with systemic sclerosis: a family-based whole exome sequencing study. Issue 1 (December 2016) - Cardinale, Christopher; Li, Dong; Tian, Lifeng; Connolly, John; March, Michael; Hou, Cuiping; Wang, Fengxiang; Snyder, James; Kim, Cecilia; Chiavacci, Rosetta; Sleiman, Patrick; Burnham, Jon; et al.
Abstract Background Systemic sclerosis (SSc) is a rheumatologic disease with a multifactorial etiology. Genome-wide association studies imply a polygenic, complex mode of inheritance with contributions from variation at the human leukocyte antigen locus and non-coding variation at a locus on chromosome 6p21, among other modestly impactful loci. Here we describe an 8-year-old female proband presenting with diffuse cutaneous SSc/scleroderma and a family history of SSc in a grandfather and maternal aunt. Methods We employed whole exome sequencing (WES) of three members of this family. We examined rare missense, nonsense, splice-altering, and coding indels matching an autosomal dominant inheritance model. We selected one missense variant for Sanger sequencing confirmation based on its predicted impact on gene function and location in a known SSc genetic locus. Results Bioinformatic analysis found eight candidate variants meeting our criteria. We identified a very rare missense variant in the regulatory NODP domain ofNOTCH4 located at the 6p21 locus, c.4245G > A:p.Met1415Ile, segregating with the phenotype. This allele has a frequency of 1.83 × 10−5 by the data of the Exome Aggregation Consortium. Conclusion This family suggests a novel mechanism of SSc pathogenesis in which a rare and penetrant coding variation can substantially elevate disease risk in contrast to the more modest non-coding variation typically found at this locus. These results suggest that modulation of theNOTCH4 gene might be responsible for the association signal at chromosome 6p21 in SSc.